Opportunities and Challenges in Implementing Artificial Intelligence in the Development of Sharia Financial Products at Bank Syariah Indonesia - Izzun Khoirun Nissa; Joko Subando; S Sulistyowati; Yuni Safitri; S Syamsuddin (Universitas Muhammadiyah Surakarta, 2025)
The development of digital technology, particularly Artificial Intelligence (AI), has driven significant transformation in the banking industry, including Islamic banking in Indonesia. Bank Syariah Indonesia (BSI), as the largest Islamic bank resulting from a merger, faces great opportunities in utilizing AI to improve operational efficiency, service quality, and risk management, while also facing challenges in maintaining compliance with Islamic principles. This study aims to analyze the opportunities and challenges of implementing AI in the development of Islamic banking products and services at Bank Syariah Indonesia, with an emphasis on operational efficiency, Sharia-based risk management, digital infrastructure readiness, and human resources. This study uses a qualitative approach with a descriptive-exploratory method. Data was obtained through a literature study of scientific articles, industry reports, policy documents, and official publications relevant to the application of AI in Islamic banking. Data analysis was conducted using qualitative descriptive methods through data reduction, data presentation, and conclusion drawing, and was reinforced with source triangulation techniques to maintain data validity. The results of the study show that AI has great potential to improve BSI's operational efficiency through business process automation, more accurate risk analysis, fraud detection, and personalized customer service. However, the implementation of AI also faces significant challenges, particularly related to data infrastructure limitations, human resource readiness, and ethical and sharia compliance issues, especially algorithm transparency and the potential for gharar due to